Analysis of Food Waste Behaviour in the Household Sector - Suci Maudy Aulia; Evi Martha (Indonesian Journal of Global Health Research, 2025)
A total of 62% of food waste comes from household waste in the world. In Indonesia, as much as 40.3% of food waste is recorded as waste generation in 2020. This problem of food waste arises from a diverse set of household behaviours. This study aims to analyze the behaviors that lead to food waste in households using Social Cognitive Theory (SCT) and Theory of Planned Behaviour (TPB). This research is using the Systematic Literature Review research method. The search was conducted using three databases namely Google Scholar, Pubmed, and ScienceDirect. The keywords used were ‘food waste’, ‘behavior’, and ‘household’. The inclusion criteria of this study were articles published since the last 5 years using English. Articles were screened using the PRISMA Framework. Food waste behaviour in household sector can occur due to various factors such as demographic, consumptive behaviour, food management knowledge and skills, psychological and consumer perceptions, and environmental and accessibility in community. The discovery of factors causing food waste through the SCT and TPB theoretical approach can help in planning more optimal and targeted health promotion interventions.